Effect of drying dynamics on the functional structure of a fish assemblage from an intermittent river network - Gonçalves-Silva, Milena; Manna, Luisa Resende; Rodrigues-Filho, Carlos Alberto Sousa; Teixeira, Francisco Keilo; Rezende, Carla Ferreira (Frontiers in Environmental Science, 2022)
We are living in a fast-changing world promoted by anthropogenic actions and ecosystems’ functioning has been constantly changed. One example is the globally reduction of river flow that can lead to more than 50% of the rivers and streams around the world becoming intermittent. However, the relationship between environmental changes and biological communities has been limited to taxonomic approach, rather than the functional approach. Functional structure determines how individuals interact with the environment and evaluating the effects of hydrological changes in functional variation can elucidate the responses of aquatic biota under climate changes. Thus, we hypothesized that hydrological phases (dry, re-wetting and wet) would influence both environmental conditions and fish composition (i.e., taxonomic richness and functional structure) in one intermittent river. In addition, we expected that: i) fish assemblages will have higher values of species richness and Functional Diversity indexes – Richness (FRic), Dispersion (FDis), Specialization (FSpe), and Originality (FOri) in drier phases (dry and re-wetting); and (ii) higher values of Functional Diversity indexes related to evenness (FEve) and divergence (FDiv) in the wet phase, due to the predominance of species with high dispersal capacity when sites are connected. Sampling was conducted in the Cruxati river during the three hydrological phases along four sites (250m each). Functional diversity analysis, involving traits of dispersion, life history and trophic ecology were used to apply Functional Diversity indexes. Indexes were compared from null models and all species were ordered in a multidimensional functional space using principal coordinate analysis (PCoA). In the dry phase, taxonomic richness and FRic between communities is higher, as well as FSpe and FOri, showing that each assemblage has unique characteristics with different strategies allowing the establishment in this hydrological phase. However, communities are less functionally dispersed. In the wet phase, when the river is connected, FDis between communities is higher and species abundances are more equitable with regular distribution in the functional space. Therefore, we conclude that local ecological processes (i.e., dynamics of hydrology) may promote the establishment of species according to their functional traits and thereby the functional structure of local assemblages.